Representasi Visual Budaya Bali Pada Komik Digital Agni - Wiguna, I Gusti Ngurah Made Aditya Priyatna Praktyaksa; Hidayat, Syarip; Zulfikar, Mohammad Ayman (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
This research discusses the visual representation of Balinese culture in the digital comic “Agni” by comic artistNy0ngbeng published on the Webtoon platform. This study aims to identify and analyze visual elements that represent Balinese culture through a descriptive qualitative approach. The analysis was conducted by using the theory of visual elements of comics according to Scott McCloud and visual semiotics of Roland Barthes. Data were obtained through observation of comic panels that feature elements of Balinese culture such as traditional clothing, architecture, traditional ceremonies, and spiritual symbols. The results show that the comic “Agni” effectively utilizes iconization, closure, panels and transitions, as well as the relationship between words and images to build a visual narrative that strengthens Balinese cultural identity. Visual semiotic analysis reveals that the denotative and connotative meanings of the visual elements in this comic not only present aesthetics, but also reinforce Balinese cultural narratives and myths in the context of digital media. Thus, the digital comic “Agni” acts as a potential media in introducing Balinese culture through modern visualizations that appeal to the younger generation.